Inequality and gender economic inclusion: The moderating role of financial access in sub-Saharan Africa - Simplice Asongu; Joseph Nnanna; Paul N. Acha-Anyi (African Governance and Development Institute (AGDI), 2019)
This study assesses how financial access can be used to modulate the effect of income inequality on gender economic inclusion. The focus is on 42 countries in sub-Saharan Africa (SSA) for the period 2004-2014 and the empirical evidence is based on Generalised Method of Moments (GMM) and Fixed Effects (FE) regressions. Significant results are not apparent in the FE regressions. The following main findings are established from the GMM estimations. There is a negative net effect from the role of financial access in modulating the effect of the Palma ratio on female labour force participation while there is a positive net effect from the relevance of financial access in moderating the effect of the Gini coefficient on female unemployment. There are also net negative effects from the role of financial access in modulating the Gini coefficient and the Palma ratio for female employment. The unexpected findings are elucidated and implications are discussed in the light of challenges to Sustainable Development Goals in the sub-region. Inter alia: financial access is a necessary but not a sufficient moderator of income inequality for the enhancement of women's participation in the formal economic sector.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Finance; Gender; Inclusive development